Tacit and Explicit Knowledge: Drivers of the Competitiveness of Universities - Ortiz Barrera, Manuel (Mercados y Negocios, 2023)
This research examines these two cognitive dimensions through a confirmatory factor analysis to determine whether their relationship with the competitiveness variable is suitable for generating genuine competitive elements. These variables have been reviewed based on available cutting-edge literature and collected a priori from Mexican higher education institutions. Cognitive elements serve as precursors to competitiveness; however, comprehending this necessitates an analysis of the cognitive asset from a dimensional perspective, wherein formal and informal knowledge criteria are scientifically established as explicit and tacit knowledge.